PENGARUH DRILL MENGGIRING BOLA TERHADAP KEMAMPUAN DRIBBLING SEPAKBOLA PADA SSB PANCA PRIMA U-15 RUMBIO JAYA - Aprizalpadli, Aprizalpadli; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is still there are flaws and weaknesses in the techniques are they exactly to dribbling the in SSB panca prima U-15 rumbio jaya. Based on the author gave the form of training drill. Research was conducted to determine how much influence the exercise drill on the ability to dribbling the football in SSB panca prima U-15 rumbio jaya. So, while carrying out dribbling the get the results of the exercise dribbling the maximum. This type of research is experimental with the design of the research one group pretest-posttest design, the population in this study is by SSB panca prima U-15 rumbio jaya, amounting to 16 people. The engineering samples are used is the total sampling. And whose entire population of 16 people in the spotlight on the sample. With the test drove the ball and then made the analysis of descriptive and a normality to use the liliefors the first significant α (0.05) produce an average of pretest a dribble of 22,10. Furthermore, given training drill during 16 sessions in SSB panca prima of 16 people. Then done posttest a dribble to produce an average of 19,12. Based on the results of date analysis pretest and posttest is no difference that the increased by 2,98. From the analysis of then’t make Tcount of 12,41 and Ttable of 1,753 isn’ tcount > ttable. It can be concluded that the training drill on the ability to dribbling the football in SSB panca prima U-15 rumbio jaya.Keywords: of drill, The ability to dribbling